La mobilité sur le campus Lyon Tech-la-Doua : approche systémique et scénarios en éco-mobilité - Philippe Terrier; Chantal Berdier; Mathieu Bouyer (Développement Durable et Territoires)
This article presents the use of a systemic approach on LyonTech- La Doua campus to propose scenarios for reducing the negative impacts of transport. A causal diagram to understand the interrelationships between the subsystems that make up the mobility system is proposed. The numerical model for impacts assessment has been developed with Vensim software®. This model is fed by data from a mobility survey conducted in 2012 on the campus. The model incorporates more than 50 variables such as transportation modes, users for each mode, speed, distance, fuel type and behavior of people on the campus in term of mobility. The numerical model was used to analyze six scenarios to mitigate impacts of mobility on the campus.